2002
DOI: 10.1073/pnas.022647699
|View full text |Cite
|
Sign up to set email alerts
|

Circulating relaxin acts on subfornical organ neurons to stimulate water drinking in the rat

Abstract: Relaxin, a peptide hormone secreted by the corpus luteum during pregnancy, exerts actions on reproductive tissues such as the pubic symphysis, uterus, and cervix. It may also influence body fluid balance by actions on the brain to stimulate thirst and vasopressin secretion. We mapped the sites in the brain that are activated by i.v. infusion of a dipsogenic dose of relaxin (25 g͞h) by immunohistochemically detecting Fos expression. Relaxin administration resulted in increased Fos expression in the subfornical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 28 publications
2
95
0
Order By: Relevance
“…Indeed, immunostaining with AngII-specific antibody revealed markedly increased AngII staining in the MHb (Figure 6Dd) and hypothalamic PVN (Figure 6Df) regions, as well as in the SFO ( Figure 6Db) of VDR(Ϫ/Ϫ) mice. Both PVN and SFO are known to be involved in regulation of water drinking 14 ; therefore, in addition to the systemic AngII, the brain-derived AngII most likely plays a critical role in the induction of water intake in VDR(Ϫ/Ϫ) mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, immunostaining with AngII-specific antibody revealed markedly increased AngII staining in the MHb (Figure 6Dd) and hypothalamic PVN (Figure 6Df) regions, as well as in the SFO ( Figure 6Db) of VDR(Ϫ/Ϫ) mice. Both PVN and SFO are known to be involved in regulation of water drinking 14 ; therefore, in addition to the systemic AngII, the brain-derived AngII most likely plays a critical role in the induction of water intake in VDR(Ϫ/Ϫ) mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated an association of increased c-Fos expression in the SFO and hypothalamic PVN neurons with stimulation of water drinking. 14 Moreover, the SFO is long known to be an important region in the brain to control water drinking in response to AngII. 15,16 To link AngII overproduction to overdrinking in VDR(Ϫ/Ϫ) mice, we examined c-Fos expression in the brain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that acute intracerebroventricular (icv) (33) or intravenous (iv) administration of RLX to rats (59) increased Fos-immunoreactivity (IR) in neurons in the SFO, organum vasculosum of the lamina terminalis, supraoptic nucleus (SON), and paraventricular nucleus of the hypothalamus (PVN), consistent with RLX-induced activation of forebrain volume regulation pathways. Some of the activated (Fos-IR) magnocellular neurons in the SON and PVN were also immunopositive for AVP or oxytocin, although the extent of activation was not quantified (33).…”
mentioning
confidence: 85%
“…RLX has been shown to activate SFO neurons that project to the PVN and SON (59,60). Importantly, the pressor response, which is often seen following acute administration of relatively high doses of RLX, is attenuated by lesion of the SFO (37) or iv administration of a V1 vasopressin receptor antagonist (40).…”
mentioning
confidence: 97%